1982
DOI: 10.1083/jcb.95.2.403
|View full text |Cite
|
Sign up to set email alerts
|

Dense bodies and actin polarity in vertebrate smooth muscle.

Abstract: The arrangement of cytoplasmic dense bodies in vertebrate smooth muscle and their relationship to the thin filaments was studied in cells from rabbit vas deferens and portal vein which were made hyperpermeable (skinned) with saponin and incubated with myosin subfragment 1 (S-1).The dense bodies were obliquely oriented, elongated structures sometimes appearing as chains up to 1.5#m in length; they were often continuous across the cell for 200 to 300 nm land were interconnected by an oblique network of 10-nm fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(89 citation statements)
references
References 43 publications
(37 reference statements)
4
82
0
3
Order By: Relevance
“…Scatterplot depicts the mean ± SD (***P < 0.0001 by paired t test from two independent and blinded observers). Smooth muscle dense bodies are thought to act as anchor points bridging the actin cytoskeleton with thin filaments (32,33), suggesting that changes in dense body characteristics reported here uncouple the actin cytoskeleton from the contractile apparatus of visceral smooth muscle-containing organs such as stomach, intestine, and bladder of Lmod1 −/− mice. Further confirmation and characterization of visceral smooth muscle nemaline-like bodies is needed in other animal models of MMIHS, as well as MMIHS patients, to establish a pathological role of these intriguing structures.…”
Section: Discussionmentioning
confidence: 83%
“…Scatterplot depicts the mean ± SD (***P < 0.0001 by paired t test from two independent and blinded observers). Smooth muscle dense bodies are thought to act as anchor points bridging the actin cytoskeleton with thin filaments (32,33), suggesting that changes in dense body characteristics reported here uncouple the actin cytoskeleton from the contractile apparatus of visceral smooth muscle-containing organs such as stomach, intestine, and bladder of Lmod1 −/− mice. Further confirmation and characterization of visceral smooth muscle nemaline-like bodies is needed in other animal models of MMIHS, as well as MMIHS patients, to establish a pathological role of these intriguing structures.…”
Section: Discussionmentioning
confidence: 83%
“…1, the model of a contractile unit of smooth muscle consists of a side-polar thick filament (6) flanked by thin filaments of opposite polarity. The thin filaments are anchored to dense bodies that are believed to be the Z-disk equivalents in smooth muscle (4,11,26,42). Our recently reported findings suggest that dense bodies may not be the Z-disk Fig.…”
Section: Modelsmentioning
confidence: 90%
“…The row-polar thick filament suggested by Hinssen et al (20) could also work for the proposed contractile unit. Evidence for the dense bodies acting as anchorage sites for the thin filaments was provided by some early studies (4,11,26,42). A recent study (46) showed that dense bodies formed long cablelike structures within smooth muscle cells and were capable of bearing passive tension.…”
Section: Assumptions Associated With the Modelsmentioning
confidence: 99%
“…Electron dense areas are also observed in the smooth muscle cell cytoplasm that are referred to as "dense bodies". They are obliquely oriented elongated structures up to 1.5 mm in length that are distributed relatively uniformly throughout the cytoplasm [6,15,23,38]. Actin filaments appear in association with virtually all cytoplasmic dense bodies.…”
Section: Cellular Organization Of Contractile Apparatusmentioning
confidence: 99%
“…Actin filaments appear in association with virtually all cytoplasmic dense bodies. The decoration of actin filaments with myosin subfragments (S-1) indicates that the filaments are oriented with the right polarity for force generation (arrowheads pointing away from the dense bodies) [15,38]. The observation that actin filaments with opposite polarity extend from either side of a given dense body has led to the suggestion that the cytoplasmic dense bodies are functionally equivalent to the Z-bands of striated muscle.…”
Section: Cellular Organization Of Contractile Apparatusmentioning
confidence: 99%